The role of gut microbiota in liver regeneration - Xu, Zhe; Jiang, Nan; Xiao, Yuanyuan; Yuan, Kefei; Wang, Zhen (Frontiers in Immunology, 2022)
The liver has unique regeneration potential, which ensures the continuous dependence of the human body on hepatic functions. As the composition and function of gut microbiota has been gradually elucidated, the vital role of gut microbiota in liver regeneration through gut-liver axis has recently been accepted. In the process of liver regeneration, gut microbiota composition is changed. Moreover, gut microbiota can contribute to the regulation of the liver immune microenvironment, thereby modulating the release of inflammatory factors including IL-6, TNF-α, HGF, IFN-γ and TGF-β, which involve in different phases of liver regeneration. And previous research have demonstrated that through enterohepatic circulation, bile acids (BAs), lipopolysaccharide, short-chain fatty acids and other metabolites of gut microbiota associate with liver and may promote liver regeneration through various pathways. In this perspective, by summarizing gut microbiota-derived signaling pathways that promote liver regeneration, we unveil the role of gut microbiota in liver regeneration and provide feasible strategies to promote liver regeneration by altering gut microbiota composition.